2019
DOI: 10.1002/hyp.13628
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the application of topographic indices in urban areas as indicators of pluvial flooding locations

Abstract: In urban areas, the presence of impervious surfaces limits natural drainage and routes water to stormwater infrastructure with finite capacity, making these areas especially prone to flooding. Though large floods are responsible for endangering lives and causing extensive damage, there is growing evidence that more frequent floods with shallow water depths, termed nuisance flooding, can have a high cumulative cost and many direct and indirect damages. To determine whether locations of nuisance flooding may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 56 publications
(78 reference statements)
0
20
0
Order By: Relevance
“…The higher TWI indicates the higher chances of getting nuisance to extreme floods in urban areas (Kelleher and McPhillips, 2020). SLR and ALOS AW3D showed the same higher value, while NED 10m and NED 30m showed strip lines in TWI maps, indicating its smoothness and small valley streams.…”
Section: Topographic Wetness Index Analysismentioning
confidence: 91%
See 4 more Smart Citations
“…The higher TWI indicates the higher chances of getting nuisance to extreme floods in urban areas (Kelleher and McPhillips, 2020). SLR and ALOS AW3D showed the same higher value, while NED 10m and NED 30m showed strip lines in TWI maps, indicating its smoothness and small valley streams.…”
Section: Topographic Wetness Index Analysismentioning
confidence: 91%
“…New York is one of the most urbanized, populated and near to coastal belt, it is prone to pluvial and low-lying (Nuisance) floods. More details of the study area can be found in other literature (Kelleher and McPhillips, 2020).…”
Section: Study Sitementioning
confidence: 99%
See 3 more Smart Citations